Analisis Faktor-Faktor Penentu Tata Kelola Pemerintahan Di Pemerintah Kota Surabaya Periode Kepemimpinan Tri Risma Harini Tahun 2015-2020 - Muhammad Quranul Kariem; Noor Ishmatuddin (Kemudi, 2021)
The Surabaya City Government under the leadership of Tri Risma Harini in the 2015-2020 period has shown various successes with indicators from the economic, development, and environmental sectors. The research method used in this study is a qualitative descriptive method with a literature review approach. The results showed that several internal and external factors of government greatly influenced the development of good governance, which had an impact on the success of governance.